On Metrization of the Topologies Induced by Fuzzy Metrics - Jianrong Wu; Hao Yang (Journal of Mathematics)
In this paper, we focus on finding the metric functions in a fuzzy metric space. After introducing the concept of a stratified function in a fuzzy metric space, we prove that the topology generated by the family of stratified functions coincides with the topology generated by the fuzzy metric. Moreover, we get the concrete form of metric function under some special conditions.